2005
DOI: 10.1152/jn.00796.2004
|View full text |Cite
|
Sign up to set email alerts
|

Akt Activation Is Necessary for Growth Factor–Induced Trafficking of Functional KCaChannels in Developing Parasympathetic Neurons

Abstract: The protein kinase Akt is a crucial regulator of neuronal survival and apoptosis. Here we show that Akt activation is necessary for mobilization of large-conductance K(Ca) channels in ciliary ganglion (CG) neurons evoked by beta-neuregulin-1 (NRG1) and transforming growth factor-beta1 (TGFbeta1). Application of NRG1 to embryonic day 9 (E9) CG neurons increased Akt phosphorylation, as observed previously for TGF(beta)1. NRG1- and TGF(beta)1-evoked stimulation of K(Ca) is blocked by inhibitors of PI3K by overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 46 publications
2
43
3
Order By: Relevance
“…Although Short-QEERL and Short-VEDEC showed similar levels of total expression, the surface expression of Short-VEDEC was markedly reduced compared with that of Short-QEERL (Fig. 4, A and B), although nonlinearities in cell surface biotinylation assays may result in the underestimation of surface expression when signals are faint (Chae et al, 2005a). Consistent with this, the whole-cell current recorded from cells expressing Short-VEDEC was also significantly reduced compared with Short-QEERL (Fig.…”
Section: A Carboxyl-terminal Trafficking Motif In Bk Channelssupporting
confidence: 68%
“…Although Short-QEERL and Short-VEDEC showed similar levels of total expression, the surface expression of Short-VEDEC was markedly reduced compared with that of Short-QEERL (Fig. 4, A and B), although nonlinearities in cell surface biotinylation assays may result in the underestimation of surface expression when signals are faint (Chae et al, 2005a). Consistent with this, the whole-cell current recorded from cells expressing Short-VEDEC was also significantly reduced compared with Short-QEERL (Fig.…”
Section: A Carboxyl-terminal Trafficking Motif In Bk Channelssupporting
confidence: 68%
“…However, from the time courses that we chose to evaluate in the present study, we cannot rule out that more immediate modifications may also be involved, such as those revealed for glutamate receptors (Levine et al, 1998;Arvanov et al, 2000;Balkowiec et al, 2000) as well as in some types of voltage-gated ion channels (Kafitz et al, 1999;Tucker and Fadool, 2002). Moreover, recent studies have shown that growth factors can alter the surface expression of both voltage-and ligand-gated ion channels via extranuclear, Akt-dependent signaling pathways (Blair et al, 1999;Brami-Cherrier et al, 2002;Wang et al, 2003;Ning et al, 2004;Chae et al, 2005). Cytoplasmic activation of signaling cascades has explicitly been demonstrated in spiral ganglion neurons to enhance their survival to depolarizing stimuli via cAMP activation of protein kinase A, possibly via the Akt effector (Bok et al, 2003); therefore, we may expect that similar mechanisms may also be in place to regulate channel surface expression in these cells.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies from our laboratory have shown that the steady-state surface expression of BK Ca channels is stimulated by growth factors in developing vertebrate neurons (Cameron et al, 1998(Cameron et al, , 2001Chae et al, 2005) and transformed cell lines (Kim et al, 2007a,b). It is noteworthy that these effects require activation of phosphoinositide 3-kinase and Akt pathways (Lhuillier and Dryer, 2002;Chae et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…It is noteworthy that these effects require activation of phosphoinositide 3-kinase and Akt pathways (Lhuillier and Dryer, 2002;Chae et al, 2005). In this regard, filamin A is a substrate for several proteins that are downstream effectors of phosphoinositide 3-kinase and Akt, including p21-activated protein kinase (Vadlamudi et al, 2002) and ribosomal S6 kinase (Woo et al, 2004).…”
Section: Discussionmentioning
confidence: 99%